GUNA DAN FUNGSI TARI PIRING PADANG MAGEK SUMATERA BARAT - Syahrial Syahrial (Institut Seni Indonesia Surakarta, 2013)
Tari Piring is a traditional art which can be found in almost every village or nagari inMinangkabau. The nagari of Padang Magek, in the Tanah Datar Regency of West Sumatra, is avillage which owns and preserves the existence of Tari Piring. The Tari Piring that is owned andmaintained by the people of Padang Magek essentially reflects the dignity of the village chief inleading and educating his people. As an integral part of the socio-cultural life of the people ofPadang Magek, this dance has a specific function and purpose associated with the object andpurpose of the performance. From the analysis that was carried out, the results obtained indicatethat Tari Piring serves as 1) the expression of emotions, 2) aesthetic appreciation, 3) entertainment,4) symbolism, 5) integration of the community, and 6) sustainability for the culture. FurthermoreTari Piring is used for 1) material culture, 2) social institutions, and 3) aestheticalpurposes.